1998
DOI: 10.3109/10731199809118943
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Autooxidation/Oxidation Mechanisms and Methemoglobin Prevention or Reduction Processes in the Bloodstream Literature review and outline of autooxidation reaction

Abstract: The amount of circulating methemoglobin in healthy humans is the result of a balance between methemoglobin production (from autooxidation and oxidation) and hemoglobin reduction. Hemoglobin autooxidation and oxidation are very complex and are not well understood. This article analyses the literature on hemoglobin autooxidation, oxidation and reduction and sets out a sequence of reactions for the oxidation of hemoglobin and the ways in which the percentage of methemoglobin is regulated or methemoglobin producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 37 publications
2
81
0
Order By: Relevance
“…both pH-and temperature dependence (10,40,64,111,120,121). Examination of Hb autoxidation rates (using both ''bench-top'' and in vivo assays) has revealed that the rate of the transition from ferrous to ferric Hb depends on several factors, including the O 2 pressure, temperature, integrity of the red blood cells, and levels of intracellular reductants and anionic effectors.…”
Section: Autoxidationmentioning
confidence: 99%
“…both pH-and temperature dependence (10,40,64,111,120,121). Examination of Hb autoxidation rates (using both ''bench-top'' and in vivo assays) has revealed that the rate of the transition from ferrous to ferric Hb depends on several factors, including the O 2 pressure, temperature, integrity of the red blood cells, and levels of intracellular reductants and anionic effectors.…”
Section: Autoxidationmentioning
confidence: 99%
“…ferrous (Fe 2+ ) Hb binding oxygen (O 2 ), is known to undergo spontaneous intramolecular oxidationreduction reactions, in which the iron is oxidized to the ferric (Fe 3+ ) form (metHb) and the oxygen is reduced to superoxide. Further reactions lead to formation of ferryl (Fe 4+ ) Hb, free heme and various ROS [6]. ROS include hydrogen peroxide and the free radicals superoxide and hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Further downstream reactions lead to formation of ferryl (Fe 4+ ) hemoglobin, free heme and various reactive oxygen species (ROS) [2]. ROS include hydrogen peroxide and the free radicals superoxide and hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%